2021
DOI: 10.3390/microorganisms9112332
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Healthcare-Associated Infections Connected to Medical Devices—An Update

Abstract: Healthcare-associated infections (HAIs) are caused by nosocomial pathogens. HAIs have an immense impact not only on developing countries but also on highly developed parts of world. They are predominantly device-associated infections that are caused by the planktonic form of microorganisms as well as those organized in biofilms. This review elucidates the impact of HAIs, focusing on device-associated infections such as central line-associated bloodstream infection including catheter infection, catheter-associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 161 publications
1
38
0
1
Order By: Relevance
“…S. epidermidis , as a common member of the human skin microbiome, can be introduced to catheters and implants during surgery and can develop biofilms on the surface of these indwelling medical devices [ 2 , 4 , 22 ]. Indwelling medical devices are vulnerable to biofilm formation by pathogens, and bacterial cells in biofilms are highly tolerant to antibiotics, which makes the eradication of biofilms extremely difficult [ 23 ]. Our previous study showed that OG significantly increases the antibiofilm activity of bacitracin against MRSA [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. epidermidis , as a common member of the human skin microbiome, can be introduced to catheters and implants during surgery and can develop biofilms on the surface of these indwelling medical devices [ 2 , 4 , 22 ]. Indwelling medical devices are vulnerable to biofilm formation by pathogens, and bacterial cells in biofilms are highly tolerant to antibiotics, which makes the eradication of biofilms extremely difficult [ 23 ]. Our previous study showed that OG significantly increases the antibiofilm activity of bacitracin against MRSA [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm-related infections represent a major clinical threat with high impact on economic costs and human health [ 1 ]. Biofilms are surface-associated microorganism communities, composed of single or multi species, embedded in an extracellular polymeric substance (EPS), secreted by the cells [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…These biofilm-related infections are difficult to threat, often requiring prolonged and combined antimicrobial therapy with poor therapeutic outcomes and a high risk of drug resistance onset. In particular, the colonization of medical devices often requires the removal and replacement of the same, leading to a prolongation of the patient’s hospitalization and an increased risk of mortality [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogenic bacteria, such as Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeruginosa , can affect people with compromised natural defenses and cause extreme systematic disease [9] . Clinical manifestations include nosocomial or healthcare-related infections, such as pneumonia, urinary infections, surgical wound infections, joint infections and septicaemia, as well as common community infections, such as intestinal, skin, soft tissue and otitis externa infections [10] .…”
Section: Introductionmentioning
confidence: 99%